Clinical-grade MRI-based methods to identify combined anatomic factors that predict ACL injury risk in male and female athletes - Beaulieu, M. L.; Nowak, E. K.; Beynnon, B. D.; Ashton-Miller, J. A.; Sturnick, D. R.; Wojtys, E. M. (The American Journal of Sports Medicine, 2021)
Background: Recently developed multivariate sex-specific statistical models can predict anterior cruciate ligament (ACL) injury risk using various knee anatomic factors. However, screening tools able to identify individuals at an increased injury risk are unlikely to be developed based on these models, given that sophisticated and time-consuming methods were used to measure those factors on research-grade resolution magnetic resonance images (MRIs).